Tinjauan Hukum atas Pembagian Harta Gono Gini Pasangan Suami Istri yang Bercerai - Mushafi, Mushafi; Faridy, Faridy (Batulis Civil Law Review, 2021)
This article discusses the legal provisions for the distribution of gono gini assets to divorced married couples. The research objective is to reveal the legal aspects and juridical provisions regarding the distribution of gono gini assets for divorced married couples. The research method used in writing this article is normative juridical. Based on the results of the research that the distribution of Gono gini assets in divorce cases and divorce cases, each husband and wife gets an equal half of the share. The gono gini distribution of assets refers to al-Quran Surat an-Nisa ayat 32, where it is stated that for all men there is a part of what they earn and all women have a share of what they earn as well.